2013
DOI: 10.1002/adfm.201302294
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of “Click”‐Phospholes Towards Self‐Assembled Luminescent Soft Materials

Abstract: Inspired by the self-assembled bilayer structures of natural amphiphilic phospholipids, a new class of highly luminescent "click"-phospholes with exocyclic alkynyl group at the phosphorus center is reported. These molecules can be easily functionalized with a self-assembly group to generate neutral "phosphole-lipids". This novel approach retains the versatile reactivity of the phosphorus center, allowing further engineering of the photophysical and self-assembly properties of the materials at a molecular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 73 publications
2
32
0
Order By: Relevance
“…Our group has also provided a recent contribution to the development of sensory materials with a cyclodextrin-based phosphole sensor. [36] In this study, we incorporated our previously reported "click" phosphole [37] and attached a cyclodextrin (28, Figure 12) known for its ability to host molecules and to induce water solubility to fluorophores. [38] This particular example was targeted at detecting molecular explosives, and the surrogate chosen for the study was picric acid.…”
Section: Sensorsmentioning
confidence: 99%
“…Our group has also provided a recent contribution to the development of sensory materials with a cyclodextrin-based phosphole sensor. [36] In this study, we incorporated our previously reported "click" phosphole [37] and attached a cyclodextrin (28, Figure 12) known for its ability to host molecules and to induce water solubility to fluorophores. [38] This particular example was targeted at detecting molecular explosives, and the surrogate chosen for the study was picric acid.…”
Section: Sensorsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] Herein we review luminescent LC materials and discuss their LC and emission properties in the context of linearly polarised electroluminescence. [21][22][23][24][25][26][27][28][29][30][31][32][33] Herein we review luminescent LC materials and discuss their LC and emission properties in the context of linearly polarised electroluminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably,inall previously studied non-hydrogen-bonded phospholes,f or which p-stacking dominates,t he molecules are assembled in af ace-to-face pattern, in which the p moieties align antiparallel to each other. [9] By contrast, the p moieties align parallel (i.e., in a syn-type fashion) in the new hydrogen-bonded system;t his feature was also found in 4c.However, as can be seen in Figure 3, the H-bonding in 4c follows az igzag pathway (dihedral angle PO-NH:4 7 8 8; Figure 4) instead of the nearly linear column found in 4a (dihedral angle PO-NH:1 318 8;F igure 4). The deviation from the linear assembly motif in 4c showcases an intriguing, novel structural feature of the hydrogen-bonded species:r otational flexibility of the phosphinamide bond.…”
mentioning
confidence: 89%